Developing Indonesia's Yoga Industry for Competitive Wellness Tourism - Safrin Arifin; Dumilah Ayuningtyas; Renny Nurhasana; Budiman Mahmud Musthofa; Bintang Mukhammad Burhanudin Akbar (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The wellness tourism industry, especially yoga, is growing rapidly, with an estimated market value of $1,974.81 billion by 2031. However, the development of this industry in Indonesia is still categorized as developing. This study aims to explore the portrait and condition of the development of the yoga industry as part of wellness tourism and identify the urgency and factors that play a role in its development. The Systematic Literature Review (SLR), which refers to the PRISMA protocol, is used to collect, analyze, and evaluate relevant documents related to the yoga industry. The analysis results show that research related to yoga and wellness tourism increased from 2015-2025, with three main clusters formed from the data analyzed. The development of the yoga industry has significant potential to improve public health and welfare and strengthen the tourism sector. The synergy the government, society, and related stakeholders need synergy to support this development.